THE CONTENT OF THE ORGANIZATION OF SPIRITUAL AND EDUCATIONAL WORK IN HIGHER EDUCATION INSTUTITIONS - Embergenov Ansatbay Paluanovich (Galaxy International Interdisciplinary Research Journal, 2021)
The relevance of the chosen topic is due to the need to pay attention to spiritual, educational and moral education in universities